Characteristic Clinicopathological Features of Secondary Extramammary Paget Disease With Underlying Anorectal Adenocarcinoma: Evenly Circumferential Perianal Distribution, Fibroepithelioma of Pinkus-like Changes, and Subepidermal Mucin Deposits Without Invasive Tumor Cells. (October 2021) - Sasaki, Yosuke; Goto, Keisuke; Sugino, Takashi; Satake, Kosuke; Yoshikawa, Shusuke; Kiyohara, Yoshio
Abstract : Abstract: This study aimed to identify the clinical and histopathological characteristics of secondary extramammary Paget disease (EMPD) with underlying anorectal adenocarcinoma so as to differentiate it from primary cutaneous EMPD. Seventeen and 8 cases of primary and secondary EMPD with anorectal adenocarcinoma, respectively, were retrieved from the pathology archive and the clinical and histopathological features reviewed. The tumor samples from 21 cases were totally resected specimens, whereas 3 and 1 of secondary and primary cases were punch biopsied, respectively. All 8 (100%) cases of secondary EMPD presented evenly distributed perianal lesions. By contrast, 4 of 17 (23.5%) primary EMPD cases had perianal skin lesions and displayed an uneven, asymmetrical distribution around the anus. Fibroepithelioma of Pinkus-like changes and subepidermal mucin deposits with no or few invasive tumor cells were observed in 6 (75%) and 3 (37.5%) of the 8 secondary EMPD cases, respectively, although 3 secondary case samples were small biopsy specimens. Both the histopathological changes were not observed in any of the 17 primary EMPD cases. Evenly circumferential perianal distribution, fibroepithelioma of Pinkus-like changes, and subepidermal mucin deposits without invasive tumor cells were characteristic to cases of secondary EMPD with anorectal adenocarcinoma. These clinicopathological features could be used to differentiate between secondary and primary EMPD.